Decomposition of Growth Factors in High-tech Industries and CO2 Emissions: After the World Financial Crisis in 2008 - Yang, Yu-Chen; Hong, Cheng-Yih; Muzayyanah, Syamsiyatul; Adha, Rishan (International Journal of Energy Economics and Policy, 2020)
Taiwan’s economic development faces two problems, one is the imbalance of the economic structure, and the other is that the industrial structure must be upgraded. This is a problem that has existed since the 1990s, but it has not been solved for a long time. The outbreak of the world financial crisis in 2008 severely damaged the international economy and finance, and Taiwan suffered a huge economic shock. In the face of an economic predicament, Taiwan attempts to transform the unbalanced economic system through technological innovation through public investment and the updating of corporate equipment, and sets the goal of sustainable development, of which high-tech industries have become the focus of economic development. This paper takes the financial crisis as the research period, analyzes the growth of the industries and their causes through the economic growth decomposition model, and estimates the CO2 emissions generated, which will help understand Taiwan’s future economic development. The research results show that the growth of high-tech industries after the financial crisis is dominated by semiconductors and power equipment-related industries. The growth factor is innovation of input technology and the improvement of self-sufficiency. At the same time, CO2 emissions are mainly caused by these two factors. Keywords: high-tech industries, CO2 emissions, input technology, growth decomposition model. JEL Classifications: Q43, C6, E2, E210 DOI: https://doi.org/10.32479/ijeep.9411